THE RELATIONSHIP OF INSTRUCTORS’ PERCEPTION TOWARDS SCHOOL DEAN’S LEADERSHIP BEHAVIOR AND THEIR JOB SATISFACTION AT HUMAN SCIENCES FACULTY IN XIANGSIHU COLLEGE GUANGXI FOR NATIONALITIES, CHINA - Mo, Yingying; Watana Vinitwatanakhun (Scholar: Human Sciences, 2022)
This study was intended to determine the relationship between Instructors’ Perception towards School Dean's Leadership Behaviors and Their Job Satisfaction at Human Sciences Faculty in Xiangsihu College Guangxi for Nationalities, China. The three objectives of this study are (1) to identify the level of instructors’ perception towards school dean's leadership behaviors; (2) to identify the level of instructors’ job satisfaction; and (3) to determine the relationship between Instructors’ Perception towards School Dean's Leadership Behaviors and Their Job Satisfaction at Human Sciences Faculty in Xiangsihu College Guangxi for Nationalities, China. The research was quantitative and correlational in design and used the Path-Goal Leadership Questionnaire and the instructors' job satisfaction using the Teachers’ Job Satisfaction Questionnaire (TJSQ). Means and Standard Deviation, and the Pearson Product Moment Correlation Coefficient were used to analyze the data for testing the hypothesis. The 80 respondents at human sciences faculty from Xiangsihu College Guangxi for Nationalities completed the questionnaire. This study found that instructors’ perception towards school dean’s leadership behaviors resulted as moderate(3.23), instructors’ job satisfaction level resulted as moderate(3.51) and there is a significant relationship between instructors’ perception towards school dean’s leadership behaviors and their job satisfaction at human sciences faculty in Xiangsihu College Guangxi for Nationalities, China. The result of Pearson correlation coefficient for the r-value was .683 with a significance value of .001. The result showed that instructors had a positive relationship between the school dean’s leadership behaviors and job satisfaction. The study provided the researcher with valuable insight and knowledge into the role of the dean’s leadership behaviors and instructors’ job satisfaction practiced in the school.